Deep‐Red Perovskite Light‐Emitting Diodes with External Quantum Efficiency Exceeding 21% Enabled by Ligand‐Modulated Dimensionality Control. Issue 20 (15th July 2022) - Liu, Zhe; Peng, Xiaomei; Xing, Shiyu; Qiu, Weidong; Li, Mengke; Shen, Chao; Sun, Guanwei; Zhou, Zhisheng; Gu, Qing; Pu, Junrong; Yang, Jiaji; Zhang, Jibin; et al.
Abstract: Quasi‐2D perovskites show great promise for light‐emitting diodes owing to suppressed non‐radiative losses enabled by the energy funneling/cascading nanostructures. However, for red emission quasi‐2D perovskites, these ideal energy landscapes for efficient perovskite light‐emitting diodes (PeLEDs) can rarely be achieved due to detrimental aggregation of the low‐dimensional ligands in perovskite precursors, leading to poor device efficiency and stability. Here, a ligand‐modulated dimensionality control strategy is explored to achieve uniform phase distribution and reduce defect density for efficient light emission. In contrast to the model phenethylammonium iodide 2D ligand, the formation of small‐ n phases can be inhibited by a structurally similar phenoxyethylammonium iodide ligand owing to the weakened aromatic stacking between ligands. Besides, the oxygen atoms can interact with the uncoordinated Pb 2+ ions and promote the NI coordination in the perovskites, which greatly reduces the non‐radiative recombination defects in the ionic lattice. With this simple and effective approach, deep‐red quasi‐2D PeLEDs with record‐high external quantum efficiency of 21.6% and decent operational stability are achieved without the need for additional additives. These results highlight the potential of ligand‐modulated dimensionality control to achieve highly efficient and stable PeLEDs with a facile fabrication process. Abstract : The oxygen atom in the phenoxyethylammonium iodide is found not only to inhibit the formation of low‐dimensional phase by weakening aromatic stacking but also to enhance the complexation with Pb 2+ . As a result, deep‐red perovskite light‐emitting diodes with record‐high external quantum efficiency of 21.6% and decent operational stability are achieved without the need for additional additives.